Safety of a pasteurized plasma‐derived Factor VIII and von Willebrand factor concentrate: analysis of 33 years of pharmacovigilance data. Issue 10 (10th July 2017) - Kouides, Peter; Wawra‐Hehenberger, Kathrin; Sajan, Anna; Mead, Henry; Simon, Toby
Abstract : BACKGROUND: Haemate‐P/Humate‐P (Humate‐P) is a pasteurized human plasma‐derived concentrate containing both Factor VIII and von Willebrand factor for treatment of hemophilia A and von Willebrand disease (VWD). STUDY DESIGN AND METHODS: We analyzed the safety of Humate‐P based on more than 33 years of postmarketing pharmacovigilance data, representing an estimated exposure of approximately 25, 000 patient‐years. The analysis comprises reports of potential adverse drug reactions (ADRs) from all sources, reported as part of routine pharmacovigilance at CSL Behring. ADRs considered clinically relevant or potential risks of Humate‐P were identified based on defined and standardized Medical Dictionary for Regulatory Activities queries. Recognizing the limitations of spontaneous reporting, we also reviewed the literature, including clinical trials with mandatory reporting. RESULTS: From 1982 to 2015, a total of 670 postmarketing cases had been reported via pharmacovigilance, for an overall reporting rate of approximately one ADR per 3900 administered standard doses. Of these cases, 343 involved ADRs considered clinically relevant risks (33 thromboembolic complications, 97 inhibitor formation, 110 hypersensitivity or allergic reactions) or potential risks (103 suspected virus transmissions) for Humate‐P. Most thromboembolic complications occurred in patients undergoing surgery or with other known risk factors. Inhibitor formation occurred mostly in patients with hemophilia A (24 cases were high titer). Most patients with hypersensitivity or allergic reactions had VWD. None of the reported suspected virus transmission cases were confirmed to be associated with Humate‐P. Reported results of company‐sponsored studies showed a low incidence of adverse events possibly or probably related to Humate‐P. CONCLUSIONS: More than 33 years of pharmacovigilance data continue to support the safety of Humate‐P.